The Indian great awakening: religion and the shaping of native cultures in early America - Fisher, Linford D. (Oxford University Press, 2012)
This text tells the story of New England's Natives' efforts to reshape their worlds between the 1670s and 1820 as they defended their land rights, welcomed educational opportunities for their children, joined local white churches during the First Great Awakening (1740s), and refashioned Christianity for their own purposes